Apostle of progress : Modesto C. Rolland, global progressivism, and the engineering of revolutionary Mexico - Castro, J. Justin, 1981- (The Mexican Experience, 2019)
From the late nineteenth century to the middle of the twentieth century, Mexico experienced major transformations influenced by a global progressive movement that thrived during the Mexican Revolution and influenced Mexico's development during subsequent governments. Engineers and other revolutionary technocrats were the system builders who drew up the blueprints, printed newspapers, implemented reforms, and constructed complexity-people who built modern Mexico with an eye on remedying long-standing problems through social, material, and infrastructural development during a period of revolutionary change.0 In Apostle of Progress J. Justin Castro examines the life of Modesto C. Rolland, a revolutionary propagandist and a prominent figure in the development of Mexico, to gain a better understanding of the role engineers played in creating revolution-era policies and the reconstruction of the Mexican nation. Rolland influenced Mexican land reform, petroleum development, stadium construction, port advancements, radio broadcasting, and experiments in political economy. In the telling of Rolland's story, Castro offers a captivating account of the Mexican Revolution and the influence of global progressivism on the development of twentieth-century Mexico.